2013
DOI: 10.1186/1742-4933-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mitochondrial biogenesis with polyphenols: combined effects of resveratrol and equol in human endothelial cells

Abstract: Emerging evidence suggests that combinatorial action of numerous biologically active compounds may be a valuable source in a variety of therapeutic applications. Several nutraceuticals have demonstrated to augment the efficacy of pharmacological approaches or provide physiological benefit to improve age-related decline. Recently, the possibilities of anti-ageing interventions have multiplied also to ameliorate the mitochondrial alterations in ageing-associated diseases. In this report, we approached a novel tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 28 publications
(27 reference statements)
1
35
1
1
Order By: Relevance
“…TFAM plays an important role in mtDNA synthesis (8). Therefore, PGC-1␣ can regulate mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TFAM plays an important role in mtDNA synthesis (8). Therefore, PGC-1␣ can regulate mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This would effectively impede the complete inhibition of mitochondrial respiration, since the binding site of kresoxim-methyl is the ubihydroquinone cytochrome-c oxidoreductase [33]. In fact, more recent studies with plant extracts showed that polyphenols could stimulate and/or enhance mitochondrial function [34][35][36]. Whether polyphenols act directly or indirectly to enhance mitochondrial functions and whether this requires binding of polyphenols to a specific receptor remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large body of research has been addressed to identify neuroprotective drugs and food supplements able to prevent neurodegenerative pathologies and preserve visual function and these efforts revealed how the use of a combination of compounds with synergistic multitarget effects might offer a significant approach for disease prevention, including neurodegenerative pathologies and retinal neurodegeneration [1,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%